Effect of nicotine chewing gum on smoking behaviour and as an aid to cigarette withdrawal. Issue 6032 (14th August 1976) - Russell, M A; Wilson, C; Feyerabend, C; Cole, P V
Abstract : In a double-blind, placebo-controlled, crossover trial the effect of 2-mg nicotine chewing gum was studied in 43 smokers when they were smoking as inclined and when they were trying to stop smoking. Although 70% of the smokers stopped smoking during treatment, only 23% were still abstinent after one year. The effect of the nicotine, though significant, was small compared with the overall reduction in smoking. When the subjects were smoking as inclined cigarette consumption was reduced by an average of 37% on the nicotine gum compared with 31% on placebo gum, while avergage carboxyhaemoglobin (COHb) levels were reduced by 26% and 15% on the active and placebo gums respectively. When subjects tried to stop smoking there was a further considerable reduction in cigarette consumption, but no longer any difference between the two gums. Nevertheless, average COHb was still lower on the active gum. Plasma nicotine levels on the nicotine gum averaged only 10-7 ng/ml compared with 27-4 ng/ml after smoking. Better results could be expected with 4-mg nicotine gums.